In Situ Fine‐Tuning of Microfluidic Chips by Swelling and Its Application to Droplet Microfluidics. Issue 8 (14th May 2019) - González‐Estefan, Juan H.; Gonidec, Mathieu; Vu, Thi Thiet; Daro, Nathalie; Chastanet, Guillaume
Abstract: Over the last two decades, polydimethylsiloxane (PDMS) has been widely used as the material of choice for fast‐throughput prototyping of microfluidic devices due to the ease of fabrication of PDMS devices by soft‐lithography replica molding methods. Nevertheless, PDMS is known to swell significantly in a variety of organic solvents which has sometimes limited its use in synthetic chemistry and has led the microfluidic community to consider PDMS as being "incompatible" with such solvents. Nevertheless, as shown here, when analyzed deeper and controlled properly, the solvent‐induced swelling of PDMS actually constitutes a potentially useful phenomenon that can become a simple tool to control and adjust finely and dynamically the geometry of microfluidic chips in situ. In this paper, this method is applied to the control of the behavior of a variety of droplet generators. The simplicity and efficiency of this approach make it a great asset for droplet microfluidics synthesis, for which microreactor sizes are a critical parameter that is often overlooked due to its complex implementation. In a more general sense, it is expected that integrating swelling into design should allow to adjust the function of many different types of chips exhibiting geometry‐driven functions. Abstract : A simple method to tune the geometry and function of microfluidic chips based on polydimethylsiloxane swelling is presented. This simple and efficient approach is a great asset for droplet microfluidics synthesis, where droplet sizes are difficult to disentangle from other experimental variables. Additionally, it could be useful to tune the behavior of other microfluidic chips with geometry‐driven functions.